Network Analysis of Temporomandibular Disorder Pain and Subject‐Based Bruxism in Post‐Traumatic Stress Disorder Patients - Chung, Joey; Knibbe, Wendy; Chattrattrai, Thiprawee; de Jongh, Ad; Lobbezoo, Frank (Journal of oral rehabilitation, 2025)
Post-traumatic stress disorder (PTSD) is a psychosocial factor of interest in the multifactorial aetiology of temporomandibular disorder (TMD) pain, awake bruxism (AB) and sleep bruxism (SB). To investigate direct and indirect associations between post-traumatic stress disorder (PTSD), TMD pain, AB, SB and demographic and psychological variables using network analysis. The study sample included 597 subjects recruited from a specialised centre for the treatment of PTSD. Network analysis was performed using a Mixed Graphical Model and included variables of self-reported TMD pain, self-reported AB, self-reported SB, age, sex, PTSD symptom severity, mood disorders, anxiety disorders and insomnia severity. These variables were visualised in the network model as nodes connected by edges, representing individual associations. The network model revealed a triangular positive association between TMD pain, AB and SB. AB also displayed a positive connection with anxiety disorders, while PTSD symptom severity was linked to insomnia, mood disorders and anxiety disorders. Age and sex did not significantly influence the network structure, although a negative association was observed between these variables, indicating younger ages among female subjects. TMD pain, AB and SB were strongly associated with each other in subjects with PTSD. The presence of anxiety disorders emerged as a bridge factor, connecting the triangular positive association between TMD pain, AB and SB with psychological conditions (PTSD severity, insomnia severity, mood disorders).